UNVEILING PATTERNS AND RATIONALES OF TEACHER’S CODE-SWITCHING IN ENGLISH LEARNING DISCOURSE - Luthfiyati, Dian; Rachmawati, Indah Aulia; Faridah, Fita; Fatmawaty, Riryn (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2026)
This study aims to unveil the patterns and rationales of code-switching employed by an English teacher during classroom interaction. Using a qualitative approach with a phenomenological method, the researcher observed the teaching-learning process in the 7th grade at SMP PGRI Sambeng. The patterns of code-switching were analyzed based on Poplack’s theory, while the rationales were examined through Hoffman’s framework and teacher interviews. The data were processed through reduction, display, and conclusion drawing. The findings revealed 42 instances of code-switching, where intra-sentential switching emerged as the dominant pattern (18 utterances), followed by tag switching (13 utterances) and intersentential switching (11 utterances). Regarding the rationales, four primary factors were identified from observations: talking about a particular topic, interjections, repetitions for clarification, and the intention of clarifyng speech content. Furthermore, interview results highlighted three contextual rationales: the students’ diverse English proficiency, the status of English as a foreign language, and the linguistic transition from elementary to junior high school. These results indicate that code-switching serves as a vital pedagogical tool to bridge communication gaps in EFL discourse.